Comprehensibility of the Accounting Information Disclosed by the Brazilian Public Sector: An Experiment Based on the Use of Popular Reporting - Leite, Kalina Kely Miranda; Diniz, Josedilton Alves (Advances in Scientific and Applied Accounting, 2024)
Purpose: To investigate the comprehensibility of the information disclosed through accounting reports from the Brazilian public sector by comparing the model mandatory disclosure with alternate disclosures from the popular reporting perspective. Method: Experimental research was used as a methodology and it was done based on scenarios with the use of a control group and three treatment groups, which encompassed the manipulation of the technical language knowledge variables and the differentiated layout based on popular reporting. Results and discussions: This paper pointed that the citizens who have no technical language knowledge but who had access to accounting information released by popular reporting know more about the accounting information disclosed by the public sector than the citizens who have technical knowledge and had access to accounting statements traditionally highlighted. Therefore, it is possible to conclude that the differentiated layout, based on popular reporting precepts, is able to overcome the lack of technical knowledge of the majority of users of the accounting information disclosed by the public sector. Contributions: Analyzing the Brazilian experience on the understandability of accounting information disclosed by the public sector from the comparison between experimental groups, this paper finds evidence that alternative ways of presenting the accounting reports disclosed by the public sector, from the use of a model based on popular reporting, overcome the lack of knowledge of technical terms used by accounting, improving the understanding of users. These findings contribute to improving the process of accountability and transparency of the accounting information disclosed by the Brazilian public sector.